Positive electrode slurry, composite positive electrode sheet, and lithium ion battery

CN116632243BActive Publication Date: 2026-11-03BEIJING WELION NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310762671.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2026-11-03
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

传统锂离子电池在热失控方面存在安全性和电化学性能不足的问题,现有添加剂在化学反应层面功能单一且耐氧化性能不佳,导致电池在高温下易发生热失控,影响电池的使用安全性和循环性能。

Method used

A positive electrode slurry containing phosphorus, fluorine, and ether-oxygen monomers is used. The positive electrode slurry, composed of positive electrode active material, binder, initiator, mixed organic additives, and initiator, forms a PF copolymer. By forming a CEI film on the surface of the positive electrode material, the thermal stability and electrochemical performance of the battery are improved.

Benefits of technology

It improves the thermal and mechanical safety performance of lithium-ion batteries, reduces interface impedance, enhances lithium-ion transport performance, reduces electrode internal resistance, and improves battery safety and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a positive electrode paste, which comprises solid substances and an organic solvent, wherein the solid substances comprise a positive electrode active material, a binder, a conductive agent, a mixed organic additive and an initiator; the mixed organic additive comprises a phosphorus-containing monomer, a fluorine-containing monomer and an ether oxygen-containing monomer. The application also provides a preparation method of a composite positive electrode film layer, a composite positive electrode sheet and a solid-state battery. The composite positive electrode sheet prepared from the positive electrode paste provided by the application can be efficiently flame-retarded, and the safety is greatly improved. The fluorine-containing monomer can improve the oxidation potential of the positive electrode sheet, and a good CEI film can be formed in the positive electrode to inhibit the oxygen evolution reaction. The polymer formed after copolymerization is similar in structure to the binder, can effectively replace a part of the binder, and the method reduces the optimization of processes and equipment, and greatly reduces the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium batteries, specifically to a positive electrode slurry, a composite positive electrode sheet, and a lithium-ion battery. Background Technology

[0002] With the continuous development of society and the economy, the new energy industry has developed rapidly, and lithium-ion batteries have been widely used in the transportation and energy storage sectors. Lithium-ion batteries have advantages such as long cycle life, high energy density, and environmental friendliness. However, with the increasing demand for energy and the growing awareness of safety, traditional lithium-ion batteries are finding it difficult to meet the demands.

[0003] Traditional lithium-ion batteries, especially ternary lithium-ion batteries, are highly sensitive to temperature. Excessive heat can easily lead to thermal runaway and safety incidents. Factors causing thermal runaway in lithium-ion batteries can generally be categorized into three types: mechanical triggering, electrical triggering, and thermal triggering. Specifically, these include physical damage to the lithium-ion battery, accidental destruction, improper use, and inherent defects. While single or multiple factors can trigger thermal runaway, inherent battery defects are often the primary cause.

[0004] To address the thermal stability and safety issues of lithium-ion batteries, adding organic additives to the positive electrode slurry is a widely used method to improve electrode safety. To enhance the thermal stability of the positive electrode, some patents employ methods that directly add polymers containing specific elements to the positive electrode slurry. Other patents utilize the unique properties of organic additives to improve electrode safety. For example, patent CN109309208B adds a thiophene-based compound to the positive electrode slurry and converts it into polythiophene through an electrochemical method. The significant increase in resistance of polythiophene with increasing temperature can significantly improve the battery's thermal safety performance. Patent CN112952100 B adds a sulfone compound containing unsaturated bonds to the positive electrode slurry. During the coating process, the sulfone compound polymerizes, forming a protective layer on the surface of the positive electrode material, reducing the reaction between the electrode material and the electrolyte, and improving the thermal stability of the cell.

[0005] Thermal runaway in batteries is often accompanied by violent chemical and electrochemical reactions, and is determined by the chemical reactions caused by crosstalk between the positive and negative electrodes. Currently widely used organic additives often address thermal runaway at the chemical reaction level; however, these additives are often single-function, have poor oxidation resistance, and are prone to decomposition and side reactions during long cycles. Furthermore, directly adding polymers to the positive electrode slurry leads to poor contact between the polymer and the positive electrode active material, increasing the internal resistance of the electrode. All these factors contribute to the deterioration of electrochemical performance, affecting the actual use of the battery. The methods of increasing the internal resistance of the electrode as described in the aforementioned patents can only reduce the impact of electrochemical reactions to a certain extent. While physical barrier methods improve battery thermal safety to some extent, the treated electrodes have poor affinity with the electrolyte, affecting the cycle performance of the cell. Therefore, a new technology is needed to solve this problem. Summary of the Invention

[0006] This application provides a positive electrode slurry and an in-situ composite positive electrode sheet to solve the above problems and significantly improve the safety and electrical performance of lithium-ion batteries.

[0007] This application provides a positive electrode slurry, which includes a solid substance and an organic solvent. The solid substance includes a positive electrode active material, a binder, a conductive agent, a mixed organic additive, and an initiator.

[0008] The mixed organic additives include phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers.

[0009] Further, in the solid material, the mass ratio of the positive electrode active material, binder, conductive agent, mixed organic additive, and initiator is 100:(0.5-5):(0.5-5):(0.05-20):(0.0001-0.2);

[0010] In the positive electrode slurry, the mass ratio of the organic solvent to the solid substance is 100:

[0011] (30-300).

[0012] Furthermore, in the mixed organic additive, the phosphorus-containing monomer is a phosphate ester compound having a double bond.

[0013] Further, in the mixed organic additive, the phosphorus-containing monomer is selected from one or more of allyl diethyl phosphate, tripropylene phosphite, allyl diethyl phosphate, allyl dimethyl phosphate, diallyl allyl phosphonate, triallyl phosphate, diethyl isopropenyl phosphate, and diethyl (2-propenyl)phosphonate, preferably triallyl phosphate, tripropylene phosphite, and diallyl allyl phosphonate.

[0014] Furthermore, in the mixed organic additive, the fluorinated monomer is a fluorinated monomer with a double bond.

[0015] Further, in the mixed organic additive, the fluorinated monomer is selected from one or more of the following: trifluoroethyl methacrylate, 2,2,2-trifluoroethyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluorobutyl methacrylate, 2,2,3,3,4,4-hexafluoro-1,5-dipentyl acrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorohexyl)ethyl methacrylate, 1H,1H-heptafluorobutyl acrylate, 2-(perfluorobutyl)ethyl methacrylate, and octafluoro-1,6-hexanediol diacrylate, preferably 1H,1H-heptafluorobutyl acrylate, octafluoro-1,6-hexanediol diacrylate, 2-(perfluorohexyl)ethyl methacrylate, and 2-(perfluorobutyl)ethyl methacrylate.

[0016] Furthermore, in the mixed organic additive, the ether-containing monomer is an acrylate monomer having an ether oxygen bond.

[0017] Further, in the mixed organic additive, the ether-containing monomer is selected from one or more of the following: tetraethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, polydipentaerythritol hexaacrylate, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, 3-methyl-1,5-pentanediol diacrylate, triethylene glycol dimethacrylate, ethoxyethoxyethyl acrylate, ethoxylated trimethylolpropane triacrylate, polybutylene glycol diacrylate, and methoxyethyl methacrylate, preferably polyethylene glycol methyl ether acrylate, polydipentaerythritol hexaacrylate, polyethylene glycol diacrylate, and polybutylene glycol diacrylate.

[0018] Further, the mass ratio of the phosphorus-containing monomer, the fluorine-containing monomer, and the ether-containing oxygen-containing monomer is 100:(30-150):(30-80), preferably 100:(50-120):(40-80).

[0019] Furthermore, the positive electrode active material is selected from one or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, binary lithium nickel cobalt oxide, binary lithium nickel manganese oxide, ternary lithium nickel cobalt manganese oxide, ternary lithium nickel cobalt aluminum oxide, and lithium manganese iron phosphate.

[0020] This application also provides a method for preparing a composite positive electrode film, which includes: coating the aforementioned positive electrode slurry onto a substrate, drying and curing it at high temperature to obtain a composite positive electrode film.

[0021] This application also provides a composite positive electrode sheet, including a composite positive electrode film and a current collector, wherein the composite positive electrode film is a composite positive electrode film prepared as described above.

[0022] The cathode slurry provided in this application involves blending fluorine-containing compounds, phosphorus-containing compounds, and ether-oxygen-containing compounds during the cathode formulation process, followed by copolymerization of these three monomers to form a PF copolymer. In this PF copolymer, the phosphorus-containing monomer effectively improves the safety of the cathode; in the event of thermal runaway, phosphorus can capture oxygen free radicals to achieve a flame-retardant effect. The fluorine-containing monomer promotes the formation of a uniform CEI film on the cathode, increases the oxidation potential, and inhibits the oxygen evolution reaction. The addition of the ether-oxygen-containing compound increases the degree of cross-linking in the system. The PF copolymer has a structure similar to PVDF, which serves as a binder, resulting in higher compatibility and the ability to effectively replace a portion of the binder, enhancing the flexibility of the electrode and reducing material loss during winding. Furthermore, the PF copolymer inhibits the oxygen evolution reaction of the cathode active material under high voltage, thereby suppressing polymer chain segment breakage. The chain segments contain ether-oxygen segments with lithium-conducting properties, which greatly improve lithium-ion transport performance and reduce interfacial impedance. Therefore, the composite cathode sheet prepared from this cathode slurry is highly flame-retardant, significantly improving safety. This method reduces the need for process and equipment optimization, and substantially reduces production costs. The in-situ polymerization process allows the polymer formed after monomer polymerization to have a closer contact with the cathode material, resulting in lower electrode impedance and less impact on slurry viscosity, thus avoiding changes in the coating process caused by changes in slurry viscosity.

[0023] The composite cathode sheet formed in situ with the cathode slurry improves the mechanical and thermal safety performance of the battery without significantly reducing the electrochemical performance. Compared with conventional cathode sheets, batteries using this composite cathode sheet formed in situ with the cathode slurry have a significantly higher thermal runaway temperature and a higher needle penetration pass rate. Detailed Implementation

[0024] The following description provides exemplary embodiments of this application, including various details to aid understanding, and should be considered merely exemplary. Therefore, those skilled in the art will recognize that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of this application. Similarly, for clarity and brevity, descriptions of well-known functions and structures are omitted in the following description.

[0025] This application provides a positive electrode slurry, comprising a solid substance and an organic solvent, wherein the solid substance comprises a positive electrode active material, a binder, a conductive agent, a mixed organic additive, and an initiator;

[0026] The mixed organic additives include phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers.

[0027] In some embodiments, the solid material comprises a positive electrode active material, a binder, a conductive agent, a mixture of organic additives, and an initiator.

[0028] In this application, the mass ratio of the positive electrode active material, binder, conductive agent, mixed organic additive, and initiator in the solid material is 100:(0.5-5):(0.5-5):(0.05-20):(0.0001-0.2).

[0029] In the positive electrode slurry, the mass ratio of the organic solvent to the solid substance is 100:

[0030] (30-300).

[0031] In some embodiments, when the mass of the positive electrode active material is 100 parts, the mass of the binder is 0.5-5 parts, the mass of the conductive agent is 0.5-5 parts, the mass of the mixed organic additive is 0.05-20 parts, preferably 0.1-15 parts, and the mass of the initiator is 0.0001-0.2 parts.

[0032] Specifically, when the mass of the positive electrode active material is 100 parts, the mass of the adhesive can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, or 5 parts.

[0033] Specifically, when the mass of the positive electrode active material is 100 parts, the mass of the conductive agent can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, or 5 parts. Specifically, when the mass of the positive electrode active material is 100 parts, the mass of the mixed organic additive can be 0.05 parts, 0.1 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts, 14.5 parts, 15 parts, 15.5 parts, 16 parts, 16.5 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 19.5 parts, or 20 parts.

[0034] Specifically, when the mass of the positive electrode active material is 100 parts, the mass of the initiator can be 0.0001 parts, 0.005 parts, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, or 0.05 parts.

[0035] Specifically, the mass ratio of the organic solvent to the solid substance can be 100:30, 100:40, 100:50, 100:60, 100:70, 100:80, 100:90, 100:100, 100:110, 100:120, 100:130, 100:140, 100:150, 100:160, 100:170, 100:180, 100:190, 100:200, 100:210, 100:220, 100:230, 100:240, 100:250, 100:260, 100:270, 100:280, 100:290, or 100:300.

[0036] In this application, the mass ratio of the phosphorus-containing monomer, the fluorine-containing monomer, and the ether-containing oxygen-containing monomer is 100:(30-150):(30-80), preferably 100:(50-120):(40-80).

[0037] In some embodiments, when the mass of the phosphorus-containing monomer is 100 parts, the mass of the fluorine-containing monomer is 30-150 parts, and the mass of the ether-oxygen-containing monomer is 30-80 parts. When the phosphorus-containing monomer content is too low, the flame retardant effect is poor; when the fluorine-containing monomer content is too low, the battery's oxidation potential decreases, making it unsuitable for high-voltage positive electrodes; when the ether-oxygen-containing monomer content is too low, the electrolyte's wettability on the electrode is poor, and the battery impedance increases. When the total content of the three monomers is too high, the battery's ionic conductivity deteriorates, and its electrical performance decreases.

[0038] In some embodiments, when the mass of the phosphorus-containing monomer is 100 parts, the mass of the fluorine-containing monomer is 50-120 parts, and the mass of the ether-containing monomer is 40-80 parts.

[0039] Specifically, when the mass of the phosphorus-containing monomer is 100 parts, the mass of the fluorine-containing monomer is 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts, or 150 parts.

[0040] Specifically, when the mass of the phosphorus-containing monomer is 100 parts, the mass of the ether-containing monomer is 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, or 80 parts.

[0041] In this application, the phosphorus-containing monomer is a phosphate ester compound having a double bond.

[0042] Specifically, the phosphorus-containing monomer is selected from one or more of allyl diethyl phosphate, tripropylene phosphite, allyl diethyl phosphate, allyl dimethyl phosphate, diallyl allyl phosphonate, triallyl phosphate, diethyl isopropenyl phosphate, and diethyl (2-propenyl)phosphonate, preferably triallyl phosphate, tripropylene phosphite, and diallyl allyl phosphonate. The increased functionality of the phosphorus-containing monomer improves its reactivity and reduces its residue. Therefore, the phosphorus-containing monomer is preferably a poly-double-bond phosphate.

[0043] In this application, the fluorinated monomer is a fluorinated monomer with a double bond.

[0044] Specifically, the fluorinated monomer is selected from trifluoroethyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluorobutyl methacrylate, 2,2,3,3,4,4-hexafluoro-1,5-dipentyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, and 2-(perfluorohexyl)ethyl methacrylate. The battery contains one or more of the following: ester, 1H,1H-heptafluorobutyl acrylate, 2-(perfluorobutyl)ethyl methacrylate, and octafluoro-1,6-hexanediol diacrylate, preferably 1H,1H-heptafluorobutyl acrylate, octafluoro-1,6-hexanediol diacrylate, 2-(perfluorohexyl)ethyl methacrylate, and 2-(perfluorobutyl)ethyl methacrylate. As the number of fluorine atoms in the fluorinated monomer increases, the oxidation potential of the battery increases, therefore monomers with a higher number of fluorine atoms are preferred.

[0045] In this application, the ether-containing monomer is an acrylate monomer having an ether oxygen bond.

[0046] Specifically, the ether-oxygen-containing monomer is selected from one or more of the following: tetraethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, polydipentaerythritol hexaacrylate, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, 3-methyl-1,5-pentanediol diacrylate, triethylene glycol dimethacrylate, ethoxyethyl acrylate, polybutylene glycol diacrylate, and methoxyethyl methacrylate, preferably polyethylene glycol methyl ether acrylate, polydipentaerythritol hexaacrylate, polyethylene glycol diacrylate, and polybutylene glycol diacrylate. When the molecular weight of the ether-oxygen-containing monomer is too low, the wettability of the electrolyte to the electrode sheet deteriorates, and the battery impedance increases. However, when its molecular weight is too high, the slurry viscosity increases, affecting the coating process. Therefore, through experiments, monomers with a molecular weight below 10,000 are preferred.

[0047] In this application, the positive electrode active material is selected from one or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, binary lithium nickel cobalt oxide, binary lithium nickel manganese oxide, ternary lithium nickel cobalt manganese oxide, ternary lithium nickel cobalt aluminum oxide, and lithium manganese iron phosphate.

[0048] In this application, the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and diethylhexyl peroxide.

[0049] In this application, the organic solvent is methylpyrrolidone or dimethylformamide.

[0050] In this application, the conductive agent is selected from acetylene black, Ketjen black, carbon nanotubes, carbon black, conductive graphite, and carbon fiber.

[0051] In this application, the adhesive is selected from at least one of PVDF, fluorinated rubber, and modified SBR rubber.

[0052] This application provides a method for preparing a composite positive electrode film, comprising: coating the aforementioned positive electrode slurry onto a substrate, drying at high temperature and curing to obtain a composite positive electrode film.

[0053] Specifically, during the preparation of the composite positive electrode film, the phosphorus-containing monomer, the fluorine-containing monomer, and the ether-containing oxygen-containing monomer react under high temperature conditions to generate a PF copolymer.

[0054] In the composite cathode film described in this application, the PF copolymer formed by the copolymerization of phosphorus-containing compounds, fluorine-containing compounds, and etheroxy compounds is applied to the composite cathode sheet to achieve flame retardancy, increase oxidation potential, and improve ionic conductivity, thereby enhancing battery safety. The resulting battery exhibits significantly reduced interfacial impedance and stable cycling performance. In the PF copolymer, the phosphorus-containing monomer effectively improves the safety of the cathode; in the event of thermal runaway, the phosphorus element can capture oxygen free radicals to achieve a flame-retardant effect. The fluorine-containing monomer promotes the formation of a uniform CEI film, increasing the oxidation potential, and the PF copolymer has a structure similar to PVDF, resulting in higher compatibility. The PF copolymer can inhibit the oxygen evolution reaction that occurs in the cathode material under high voltage, thereby inhibiting the breakage of polymer chain segments. The addition of etheroxy compounds increases the degree of crosslinking in the system, can replace part of the binder, and contains etheroxy segments with lithium-conducting properties, which can greatly improve lithium-ion transport performance and reduce interfacial impedance.

[0055] This application also provides a composite positive electrode sheet, including the aforementioned composite positive electrode film and a current collector, wherein the composite positive electrode film is the aforementioned composite positive electrode film.

[0056] Test method:

[0057] Linear sweep voltammetry (LSV test): Assembled lithium-ion stainless steel button cells and tested them using linear sweep voltammetry in an electrochemical workstation with a voltage range of 2.75-6V and a scan rate of 1mV / s.

[0058] Cell electrical performance testing: The soft-pack cells obtained above were subjected to 0.1C charge-discharge testing using Wuhan Blue Point charge-discharge equipment, with a voltage range of 2.75-4.25V;

[0059] Thermal runaway test: The soft pack battery was tested using a special heating test oven for lithium-ion batteries. The heating rate was 5℃ / min. After reaching 130℃, the temperature was increased by 10℃ and held for 1 hour. The cutoff temperature was 200℃.

[0060] Needle penetration test: The test is conducted at an ambient temperature of 20℃. The lithium battery connected to a thermocouple is placed in a fume hood, and a non-corrosion steel needle with a diameter of 2-8mm is used to pierce the center of the largest surface of the battery at a speed of 10mm / s-40mm / s, and held for 5 seconds. The battery is considered qualified if it does not explode or catch fire.

[0061] Implementation Examples and Test Sections

[0062] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0063] I. Implementation Examples

[0064] Example 1

[0065] 25g triallyl phosphate, 15g octafluoro-1,6-hexanediol diacrylate, 10g polyethylene glycol diacrylate, 0.5g azobisisobutyronitrile, 429.5g NCM 811, 175g NMP, 10g PVDF, and 10g SuperP were uniformly mixed to obtain a positive electrode slurry. The amount of mixed organic additives (composed of triallyl phosphate, octafluoro-1,6-hexanediol diacrylate, and polyethylene glycol diacrylate) was 10wt% (in the examples, the amount of mixed organic additives refers to the mass percentage of the mixed organic additives in the solid matter). The positive electrode slurry was coated on aluminum foil, vacuum dried, and cured to obtain a composite positive electrode sheet. The composite positive electrode sheet was then assembled into a soft-pack battery cell, injected with electrolyte, and finally prepared into a soft-pack battery cell with a composite positive electrode. A soft-pack cycle test was then performed, with the electrolyte being the basic electrolyte (1M LiPF6 in...). EC / EMC (1:1 invol) was used with a PP single-layer microporous membrane and a silicon-carbon 450 anode. The oxidation potential was tested by linear sweep voltammetry, and the safety performance was tested by needle penetration test and hot box test. The parameters are shown in Table 1.

[0066] Example 2

[0067] Example 2 differs from Example 1 in the amount of initiator, positive electrode active material, and mixed organic additives. 0.125g triallyl phosphate, 0.075g octafluoro-1,6-hexanediol diacrylate, 0.05g polyethylene glycol diacrylate (i.e., 0.25g mixed organic additives), 0.0025g azobisisobutyronitrile, 479.75g NCM 811, 175g NMP, 10g PVDF, and 10g SuperP were uniformly mixed to obtain a positive electrode slurry. The amount of mixed organic additives in Example 2 was 0.05wt%. The remaining conditions were the same as in Example 1 for preparing the soft-pack battery cell, and the same testing methods were used. The parameters are shown in Table 1.

[0068] Example 3

[0069] The difference between Example 3 and Example 1 lies in the different amounts of initiator, positive electrode active material, and mixed organic additives. 12.5g of triallyl phosphate, 7.5g of octafluoro-1,6-hexanediol diacrylate, 5g of polyethylene glycol diacrylate (i.e., 25g of mixed organic additives), 0.25g of azobisisobutyronitrile, 454.75g of NCM 811, 175g of NMP, 10g of PVDF, and 10g of SuperP were uniformly mixed to obtain a positive electrode slurry. The amount of mixed organic additives in Example 3 was 5wt%. The remaining conditions were the same as in Example 1 to prepare the soft-pack battery cell. The cells were tested using the same method, and the parameters are shown in Table 1.

[0070] Example 4

[0071] Example 4 differs from Example 1 in the amount of initiator, positive electrode active material, and mixed organic additives. 37.5g triallyl phosphate, 22.5g octafluoro-1,6-hexanediol diacrylate, 15g polyethylene glycol diacrylate (i.e., 75g mixed organic additives), 0.75g azobisisobutyronitrile, 404.25g NCM 811, 175g NMP, 10g PVDF, and 10g SuperP were uniformly mixed to obtain a positive electrode slurry. The amount of mixed organic additives in Example 4 was 15wt%. The remaining conditions were the same as in Example 1 for preparing the soft-pack battery cell, and the same methods were used for testing. The parameters are shown in Table 1.

[0072] Example 5

[0073] Example 5 differs from Example 1 in the amount of initiator, positive electrode active material, and mixed organic additives. 50g of triallyl phosphate, 30g of octafluoro-1,6-hexanediol diacrylate, 20g of polyethylene glycol diacrylate, 1g of azobisisobutyronitrile, 379g of NCM 811, 175g of NMP, 10g of PVDF, and 10g of SuperP were uniformly mixed to obtain a positive electrode slurry. The amount of mixed organic additives in Example 5 was 20wt%. The remaining conditions were the same as in Example 1 to prepare a soft-pack battery cell. The cells were tested using the same method, and the parameters are shown in Table 1.

[0074] Example 6

[0075] Example 6 differs from Example 1 in the amount of initiator, positive electrode active material, and mixed organic additives. 62.5g triallyl phosphate, 37.5g octafluoro-1,6-hexanediol diacrylate, 25g polyethylene glycol diacrylate, 1.25g azobisisobutyronitrile, 353.75g NCM 811, 175g NMP, 10g PVDF, and 10g SuperP were uniformly mixed to obtain a positive electrode slurry. The amount of mixed organic additives in Example 6 was 25wt%. The remaining conditions were the same as in Example 1 to prepare a soft-pack battery cell. The cells were tested using the same method, and the parameters are shown in Table 1.

[0076] Example 7

[0077] The difference between Example 7 and Example 1 is that the type of phosphorus-containing monomer is different. In Example 7, the phosphorus-containing monomer is replaced with diethyl allyl phosphate. The other conditions are the same as in Example 1 to prepare the soft-pack battery cell. The cells are tested using the same method, and the parameters are shown in Table 2.

[0078] Example 8

[0079] Example 8 differs from Example 1 in that it uses a different type of fluorinated monomer. In Example 8, the fluorinated monomer is replaced with 2,2,2-trifluoroethyl acrylate. All other conditions are the same as in Example 1 for preparing the pouch cell. The cells were tested using the same method, and the parameters are shown in the table.

[0080] Example 9

[0081] The difference between Example 9 and Example 1 is that the type of fluorinated monomer is different. In Example 9, the fluorinated monomer is replaced with 2-(perfluorohexyl)ethyl methacrylate. The other conditions are the same as in Example 1 to prepare the soft-pack battery cell. The cells are tested using the same method, and the parameters are shown in Table 2.

[0082] Example 10

[0083] The difference between Example 10 and Example 1 is that the types of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. In Example 10, the phosphorus-containing monomer is diallyl allyl phosphonate, the fluorine-containing monomer is 1H,1H-heptafluorobutyl acrylate, and the ether-oxygen-containing monomer is polydipentaerythritol hexaacrylate. The other conditions are the same as in Example 1 for preparing the soft-pack battery cell, and the same method is used for testing. The parameters are shown in Table 2.

[0084] Example 11

[0085] The difference between Example 11 and Example 1 is that the types of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. In Example 11, the phosphorus-containing monomer is tripropylene phosphite, the fluorine-containing monomer is 2-(perfluorobutyl)ethyl methacrylate, and the ether-oxygen-containing monomer is polyethylene glycol methyl ether acrylate. The remaining conditions are the same as in Example 1 for preparing the soft-pack battery cell, and the same method is used for testing. The parameters are shown in Table 2.

[0086] Example 12

[0087] The difference between Example 12 and Example 1 is that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:30:30, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 for preparing soft-pack battery cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0088] Example 13

[0089] The difference between Example 13 and Example 1 is that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:50:50, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 for preparing soft-pack cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0090] Example 14

[0091] Example 14 differs from Example 1 in that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:100:60, and the total mass of the mixed organic additives in Example 1 is 50g. The remaining conditions are the same as in Example 1 for preparing soft-pack cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0092] Example 15

[0093] The difference between Example 15 and Example 1 is that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:120:80, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 for preparing soft-pack cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0094] Example 16

[0095] The difference between Example 16 and Example 1 is that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:150:80, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 for preparing soft-pack cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0096] Example 17

[0097] The difference between Example 17 and Example 1 is that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:10:120, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 for preparing soft-pack cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0098] Example 18

[0099] The difference between Example 18 and Example 1 is that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:190:10, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 for preparing soft-pack cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0100] Example 19

[0101] The difference between Example 19 and Example 1 is that the proportions of phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers are different. The mass ratio of the phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers is 100:200:200, which satisfies the requirement that the total mass of the mixed organic additives in Example 1 is 50g. The remaining conditions are the same as in Example 1 for preparing soft-pack battery cells, and the same methods are used for testing. The parameters are shown in Table 3.

[0102] Comparative Example 1

[0103] The difference between Comparative Example 1 and Example 1 is that no mixed organic additives or initiators are added. 480g NCM811, 175g NMP, 10g PVDF and 10g SuperP are uniformly mixed to obtain a positive electrode slurry. The remaining conditions are the same as in Example 1 to prepare a soft-pack battery cell. The same method is used for testing, and the parameters are shown in Table 4.

[0104] Comparative Example 2

[0105] The difference between Comparative Example 2 and Example 1 is that no phosphorus-containing monomer is added, the content of the fluorine-containing monomer is 30g, the content of the ether-oxygen-containing monomer is 20g, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 to prepare the soft-pack battery cell, and the same method is used for testing. The parameters are shown in Table 4.

[0106] Comparative Example 3

[0107] The difference between Comparative Example 3 and Example 1 is that no fluorine-containing monomer is added, the content of the phosphorus-containing monomer is 35g, the content of the ether-oxygen-containing monomer is 15g, and the total mass of the mixed organic additives in Example 1 is 50g. The other conditions are the same as in Example 1 to prepare the soft-pack battery cell, and the same method is used for testing. The parameters are shown in Table 4.

[0108] Comparative Example 4

[0109] The difference between Comparative Example 4 and Example 1 is that no ether-containing monomer is added. The content of the phosphorus-containing monomer is 31.25g and the content of the fluorine-containing monomer is 18.75g. The other conditions are the same as those in Example 1 for preparing the soft-pack battery cell. The cells are tested using the same method, and the parameters are shown in Table 4.

[0110] Comparative Example 5

[0111] The difference between Comparative Example 5 and Example 1 is that no fluorine-containing monomer and ether-containing oxygen-containing monomer are added, and the content of the phosphorus-containing monomer is 50g. The other conditions are the same as those in Example 1 to prepare the soft-pack battery cell. The same method is used for testing, and the parameters are shown in Table 4.

[0112] Comparative Example 6

[0113] The difference between Comparative Example 6 and Example 1 is that no phosphorus-containing monomer and ether-containing oxygen-containing monomer are added, and the content of the fluorine-containing monomer is 50g. The other conditions are the same as those in Example 1 to prepare the soft-pack battery cell. The same method is used for testing, and the parameters are shown in Table 4.

[0114] Comparative Example 7

[0115] The difference between Comparative Example 7 and Example 1 is that no phosphorus-containing monomer or fluorine-containing monomer is added, and the content of the ether-containing oxygen monomer is 50g. The other conditions are the same as those in Example 1 to prepare the soft-pack battery cell. The same method is used for testing, and the parameters are shown in Table 4.

[0116] Comparative Example 8

[0117] The difference between Comparative Example 8 and Example 1 is that 25g of triallyl phosphate, 15g of octafluoro-1,6-hexanediol diacrylate, 10g of polyethylene glycol diacrylate, and 0.5g of azobisisobutyronitrile were first uniformly mixed and cured in an oven at 60°C for 18h to obtain a polymer additive. Then, the polymer additive prepared by the non-in-situ method, 429.5g of NCM 811, 175g of NMP, 10g of PVDF, and 10g of SuperP were uniformly mixed to obtain a positive electrode slurry. The remaining conditions were the same as in Example 1 to prepare a soft-pack battery cell. The cells were tested using the same method, and the parameters are shown in Table 5.

[0118] II. Testing Section

[0119] 1. Table 1 shows the effect of different blending amounts of mixed organic additives.

[0120] Example % of blending Cycle @ retention rate Battery impedance after formation / mΩ LSV / V Acupuncture pass rate % Hot box runaway temperature / ℃ 1 10 680 5.5 4.6 100 200 2 0.05 620 5.1 4.3 70 150 3 5 650 5.3 4.4 100 170 4 15 650 5.6 4.6 100 190 5 20 590 6.5 4.6 100 190 6 25 370 8.2 4.5 100 180

[0121] As shown in the table above, by comparing Examples 1-6, the mixing amount of the mixed organic additive has a suitable range. The battery performance can meet the requirements of use when the mixing amount, that is, the mass percentage of the mixed organic additive in the solid material is between 0.05% and 20%, and the battery stability is relatively high. The optimal mixing amount is 0.1%-15%, the needle penetration pass rate can reach 100%, and the thermal runaway temperature can reach 200°C.

[0122] 2. Table 2 shows the effect of different monomer functionalities.

[0123]

[0124] As shown in the table above, when the functionality of phosphorus-containing monomers decreases, the monomer reactivity decreases, resulting in monomer residues and easy oxidation of double bonds, which leads to a decrease in the electrochemical window of the battery. Therefore, phosphorus-containing monomers with multiple double bonds are preferred.

[0125] By comparing Examples 1, 8 and 9, it can be seen that as the number of fluorine atoms in the fluorine-containing monomer increases, the oxidation potential of the battery increases.

[0126] 3. Table 3 shows the effect of different mass ratios of the three monomers.

[0127]

[0128] As shown in the table above, comparing Examples 1 and 12-19, it is evident that changing the ratio of the three types of monomers has a significant impact on battery performance and safety. Increasing the proportion of phosphorus-containing monomers improves battery safety; increasing the proportion of fluorine-containing monomers increases the battery's oxidation potential; increasing the proportion of ether-oxygen-containing monomers reduces battery impedance, but decreases the battery's mechanical strength.

[0129] The optimal range for the monomer ratio is between 100:(50-120):(40-80), but the range for the monomer mass ratio is also between 100:(30-150):(30-80) to meet the usage requirements.

[0130] 4. Table 4 shows the effects of mixed organic additives with different compositions that are not within the scope of this application.

[0131]

[0132] As can be seen from the above, by adding mixed organic additives to the positive electrode slurry, the soft-pack battery cells prepared from this positive electrode material have high electrical performance and safety performance.

[0133] By comparing Example 1 and Comparative Example 1, it can be seen that the method provided in this application has a significant improvement in electrical performance and safety performance compared with the additive-free system in Comparative Example 1.

[0134] By comparing Example 1 and Comparative Examples 2-7, when no phosphorus-containing monomer was added to the mixed organic additive, the safety performance of the pouch cell decreased significantly; when no fluorine-containing monomer was added to the mixed organic additive, the oxidation potential of the pouch cell decreased; when no ether-containing monomer was added to the mixed organic additive, the conductivity of the pouch cell decreased; compared to the presence of the three monomers individually or in pairs, the synergistic effect of the three monomers significantly improved the safety performance of the battery.

[0135] 5. Table 5 shows the effects of three monomer curing methods.

[0136]

[0137] As shown in the table above, the polymer adheres tightly to the positive electrode active material through in-situ curing polymerization, which reduces the internal resistance of the electrode and gives the battery better cycle performance.

[0138] Although the embodiments of this application have been described above in conjunction with the specific embodiments described, this application is not limited to the specific embodiments and application fields described above. The specific embodiments described above are merely illustrative and instructive, and not restrictive. Those skilled in the art can make many other forms based on the teachings of this specification and without departing from the scope of protection of the claims of this application, and these are all within the scope of protection of this application.

Claims

1. A positive electrode slurry, wherein, It includes solid substances and organic solvents, wherein the solid substances include positive electrode active materials, binders, conductive agents, mixed organic additives, and initiators; The mixed organic additives include phosphorus-containing monomers, fluorine-containing monomers, and ether-oxygen-containing monomers; The phosphorus-containing monomer is a polydouble-bonded phosphate ester; The fluorinated monomer is a fluorinated monomer with a double bond; The mass ratio of the phosphorus-containing monomer, the fluorine-containing monomer, and the ether-oxygen-containing monomer is 100:(30-150):(30-80). The fluorinated monomer is selected from one or more of the following: trifluoroethyl methacrylate, 2,2,2-trifluoroethyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluorobutyl methacrylate, 2,2,3,3,4,4-hexafluoro-1,5-dipentyl acrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorohexyl)ethyl methacrylate, 1H,1H-heptafluorobutyl acrylate, 2-(perfluorobutyl)ethyl methacrylate, and octafluoro-1,6-hexanediol diacrylate. In the positive electrode formulation process, fluorine-containing monomers, phosphorus-containing monomers, and ether-containing monomers are mixed. The three monomers are copolymerized through in-situ curing polymerization to form PF copolymers.

2. The positive electrode slurry according to claim 1, wherein, In the solid material, the mass ratio of the positive electrode active material, binder, conductive agent, mixed organic additive, and initiator is 100:(0.5-5):(0.5-5):(0.05-20):(0.0001-0.2). In the positive electrode slurry, the mass ratio of the organic solvent to the solid substance is 100:(30-300).

3. The positive electrode slurry according to claim 1, wherein, The phosphorus-containing monomer is selected from one of triallyl phosphate, tripropylene phosphite, and diallyl allyl phosphonate.

4. The positive electrode slurry according to claim 1, wherein, The fluorinated monomer is selected from one of 1H,1H-heptafluorobutyl acrylate, octafluoro-1,6-hexanediol diacrylate, 2-(perfluorohexyl)ethyl methacrylate, and 2-(perfluorobutyl)ethyl methacrylate.

5. The positive electrode slurry according to claim 1, wherein, In the mixed organic additive, the ether-containing monomer is an acrylate monomer having an ether oxygen bond.

6. The positive electrode slurry according to claim 5, wherein, In the mixed organic additive, the ether-containing monomer is selected from one or more of the following: tetraethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, polydipentaerythritol hexaacrylate, ethylene glycol dimethacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, 3-methyl-1,5-pentanediol diacrylate, triethylene glycol dimethacrylate, ethoxyethyl acrylate, ethoxylated trimethylolpropane triacrylate, polybutylene glycol diacrylate, and methoxyethyl methacrylate.

7. The positive electrode slurry according to claim 6, wherein, The ether-containing monomer is selected from one of polyethylene glycol methyl ether acrylate, polydipentaerythritol hexaacrylate, polyethylene glycol diacrylate, and polybutylene glycol diacrylate.

8. The positive electrode slurry according to claim 1, wherein, The mass ratio of the phosphorus-containing monomer, the fluorine-containing monomer, and the ether-containing oxygen-containing monomer is 100:(50-120):(40-80).

9. The positive electrode slurry according to claim 1, wherein, The positive electrode active material is selected from one or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, binary lithium nickel cobalt oxide, binary lithium nickel manganese oxide, ternary lithium nickel cobalt manganese oxide, ternary lithium nickel cobalt aluminum oxide, and lithium manganese iron phosphate.

10. A method for preparing a composite positive electrode film, wherein, include: The positive electrode slurry described in any one of claims 1-9 is coated onto a substrate, dried at high temperature and cured to obtain a composite positive electrode film.

11. A composite positive electrode, comprising a composite positive electrode film and a current collector, wherein, The composite positive electrode film is the composite positive electrode film prepared according to claim 10.

Citation Information

Patent Citations

  • Positive electrode slurry, positive electrode sheet and electrochemical energy storage device

    CN109309208B

  • Polymer modified positive pole piece, preparation method thereof and lithium battery

    CN115692606A

  • Positive electrode slurry for lithium slurry battery and preparation method of positive electrode slurry

    CN115863541A